A comparison of geomorphic settings, sediment facies and benthic habitats of two carbonate systems of Western Mediterranean Sea and South Western Australia: Implications for coastal management - Tecchiato, Sira; Buosi, C.; Ibba, A.; Ryan, D.; De Muro, S. (2016)
© Coastal Education and Research Foundation, Inc. 2016.A similarity exists between the coastal areas of South Western Australia and South Sardinia (Italy-Western Mediterranean Sea), as temperate water carbonate sedimentation dominates the inner shelf at these locations. The seagrass carbonate factory regulates the deposition of modern bioclasts, and the distribution of seagrass meadows and accumulation of bioclasts is controlled by similar processes at the study sites. These biogenic components are mixed to quartz-feldspar sands producing significantly comparable sediment facies, which have been previously documented for Esperance Bay (South Western Australia) and off Porto Pino beaches (Sardinia). Whilst the geological settings of these areas show similar outcropping lithologies, the clastic component of these mixed biogenic and quartz-feldpar sand facies is transported by different agents in the Australian and Sardinian site. In this paper, the similarity between sediment facies is highlighted and their comparison has produced new insights into the processes regulating sediment accumulation in two hydrodynamically different embayments. The characteristics of seagrass beds and their link to the beach system are also compared and set within the context of Mediterranean and South Australian bioregions. These outcomes are relevant for beach management, as European and Australian environmental regulations are compared herein.